Derivatizations of Sgc8‐c aptamer to prepare metallic radiopharmaceuticals as imaging diagnostic agents: Syntheses, isolations, and physicochemical characterizations. (24th November 2017) - Sicco, Estefanía; Báez, Jessica; Margenat, Jimena; García, Fernanda; Ibarra, Manuel; Cabral, Pablo; Moreno, María; Cerecetto, Hugo; Calzada, Victoria
Abstract : Aptamers, oligonucleotides with the capability to bind to a target through non‐covalent bonds with high affinity and specificity, have a great number of advantages as scaffold to prepare molecular imaging agents. In this sense, we have performed post‐SELEX modifications of a truncated aptamer, Sgc8‐c, which bind to protein tyrosine kinase 7 to obtain a specific molecular targeting probe for in vivo diagnosis and in vivo therapy. Herein, we describe the synthetic efforts to prepare conjugates between Sgc8‐c and different metallic ions chelator moieties in short times, high purities, and adequate yields. The selected chelator moieties, derived from 1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid, 2‐benzyl‐1, 4, 7‐triazacyclononane‐1, 4, 7‐triacetic acid, and 6‐hydrazinonicotinic acid, were covalently attached at the 5′‐aptamer position yielding the expected products which were stable in aqueous solution up to 75°C and in typical aptamer storage conditions at least for 30 days. Abstract : Post‐SELEX modifications on Sgc8‐c aptamer, in order to prepare conjugate for further transformations to radiopharmaceuticals, are described.